AUTOMATED GENERATION OF PART PROCESSING CODES ON CNC MACHINES - SOKOLAN, IULIIA; LARIONOV, IVAN; MAIDAN, PAVLO; SOKOLAN, KATERYNA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
In modern realities, the process of generating codes for CNC machines is carried out manually, or the machine operator writes the code for the CAD model that was designed at the previous stage. At the next stage, the CNC machine code is simulated for further checking for errors, i.e., the code is compiled. This stage is mandatory before starting work and machining parts on CNC machines. Writing and subsequent calibration of the code for a CNC machine is a rather laborious procedure. It should be noted that most of the time is spent on the stage of working with CAD/CAM models and CNC operations performed manually. This problem significantly slows down the process of machining parts on CNC machines. The key to solving this problem is to automate the process of generating code for a CNC machine. The paper proposes the use of a developed script, the result of which is the automatic generation of part processing codes. Such scripts can be used in the future to process parts on machines from different manufacturers. In addition, a comparison of the part processing codes generated in the Catia V5 software and the codes generated automatically is carried out. As a result, it was found that the use of an automatic approach is more flexible, since a change in the geometric parameters of parts causes an automatic change in the machining code of such a part, in contrast to the codes created in Catia V5, in which, with a minimal change in the dimensions of the part, it is necessary to repeat the entire process of creating a machining code.